WAYS TO INCREASE EFFICIENCY IN THE SPHERE OF TOURISM USING INTERNET MARKETING METHODS - Shaikhimanov Nurdaulet Gayratdin coals (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: The article examines key Internet marketing methods that contribute to increased efficiency in the tourism industry. The main focus is on website optimization, content marketing, the use of social networks, email marketing, contextual and targeted advertising, working with reviews and ratings, as well as video marketing and virtual tours. The importance of analytics and process automation for improving customer interactions and increasing the competitiveness of travel companies is emphasized .